Dinamika Pasang Surut dan Kualitas Perairan Sungai Tabanio Kabupaten Tanah Laut Kalimantan Selatan - Sofarini, Dini; Yunandar, Yunandar; Asmawi, Suhaili; Dharmaji, Deddy; Rahim, Nur Fadhilah; Syahnakri, Erwan; Apriansyah, Farhan (Universitas Trunojoyo Madura, 2024)
The tidal dynamics of water affect not only the layers on the surface of the seas but also the entire water mass. The Tabanio River is a tidal-influenced water area with the highest utilisation level in Tanah Laut. Water quality at the estuaries of Tabanio and Panjaratan River is affected by various human activities, such as fishing, plantations, transportation, and waste disposal. This study aims to compare water quality at high and low tides and test the relationship between tidal changes and fluctuations in water quality parameters in both locations. The data used are the results of measurements on July 3 and July 22, 2024, during high and low tide conditions. The relationship between water quality values and tides was analyzed descriptively, then compared with water quality standards according to Government Regulation of the Republic of Indonesia Number 22 of 2021 class 1 and continued with the ANOVA test. Low tide conditions bring to increase in the parameters of conductivity, current, temperature, pH, salinity, and TDS at all locations, while turbidity is only in the estuary. Tidal conditions influence oxygen deficits in all sites, while nitrite and nitrate tend to increase. TSS parameters exceed quality standards in Panjaratan, while Cu and COD exceed quality standards in Tabanio.